Short report: Clonic hemifacial spasm from posterior fossa arteriovenous malformation. Issue 7 (July 1979) - Pierry, Adrian; Cameron, Malcolm
Abstract : A 21 year old woman presented with a two year history of right sided clonic hemifacial spasm. Investigations showed a large arteriovenous malformation on the right side of the posterior fossa and surgical exploration was undertaken. Early follow-up at six months showed a complete cure.